Detection of Antibiotics Resistance Genes and Molecular Characterization of Salmonella spp from Clinical and Poultry Samples in Yenagoa Metropolis of Bayelsa - D, Eboh D.; V, Anyiam I. (African Journal of Sciences and Traditional Medicine, 2024)
Salmonellae are facultative anaerobes, intracellular Gram-negative motile bacteria. They are one of the most important zoonotic pathogens transmitting among humans and animals and are responsible for high cases of morbidity and mortality in a wide range of hosts. Due to the similarity of antibiotic classes used to treat animals and humans, there is a high risk for the emergence of the multi-drug resistant (MDR) strains. Thus, this study was aimed at detection of antibiotics resistance genes and molecular characterization of Salmonella spp from clinical and livestock samples. Hundred (100) stool samples comprising of fifty (50) clinical and fifty (50) poultry were respectively collected from Federal Medical Centre (FMC) Yenagoa, Niger Delta University Teaching Hospital (NDUTH), Okolobiri, Diette Koki hospital, Opolo, and poultry farms at Swali, Kpansia and Azikoro. The samples were analyzed by culture using various enrichment, selective and differential media (selenite F broth, bismuth sulphite agar and MacConkey agar), biochemical tests, and molecular methods. Eleven (11) isolates were recovered from the samples comprising of two (2) clinical and nine (9) poultry, and resulting in a prevalence of 4% and 18% respectively. The result of the antibiotic profile showed that all isolates were multi drug resistant to ceftriaxone (63.6%), ofloxacin (0%), gentamicin (9.1%), co-trimoxazole (36.4%), levofloxacin (9.1%), clindamycin (90.9%), augmentin (72.7%), cefixime (100%), nitrofurantoin (100%), tazobactam/piperacillin (72.7%) and ciprofloxacin (18.2%). Following the biofilm test analysis, none of the recovered isolates is a biofilm former hence, there is no relationship between biofilm formation and the high level of resistance recorded. Screening for the presence of resistance genes revealed that 83.3% of the isolates have tet A. 66.7% have SHV gene while 16.7% have VEB and NDM genes respectively. This depicts a strong correlation between the observed high level of antimicrobial resistance amongst the isolates and prevalence of resistance genes. The phylogenetic analysis result showed that the evolutionary distances as computed were in agreement with the phylogenetic placement of the 16S rRNA of the isolates within the Salmonella, Shigella and Proteus spp and revealed a closely relatedness to the Salmonella enterica, Shigella flexneri, Proteus columbae and Proteus cibarius. The study established that only the fluoroquinolones and aminoglycosides can be relied upon in the effective treatment of infections with MDR Salmonella, Shigella and Proteus spp and restriction of indiscriminate use of antibiotics in food animals will be an effective measure to stop/prevent uncontrollable outbreaks of infections due to these isolates even as antibiogram results are constantly monitored worldwide.